Audit Sektor Publik sebagai Instrumen Penguatan Good Governance dalam Pengelolaan Keuangan Publik (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
Public sector audits play a strategic role in supporting the realization of good governance, particularly in public financial management, which demands high levels of accountability, transparency, effectiveness, and efficiency. Increasing public demands for clean and accountable governance have made good governance practices a fundamental requirement in the public sector. However, in practice, there are still various problems, such as weak supervision, low compliance with regulations, and suboptimal follow-up on audit results in public financial management. This article aims to conceptually analyze the role of public sector auditing as an instrument for strengthening good governance in public financial management. The research method used is a qualitative approach with a conceptual paper type, through the review and synthesis of theories, regulations, and previous research results relevant to public sector auditing, good governance, and public financial management. The conceptual framework is built based on public sector agency theory, stewardship theory, and public accountability theory, which view auditing as a mechanism for control and accountability in the relationship between the government and the public. The results of the conceptual study show that public sector audits contribute significantly to strengthening the principles of good governance through increased transparency, accountability, and the effectiveness and efficiency of public financial management, supported by the independence and competence of auditors, compliance with audit standards, and the effectiveness of audit follow-up, so that public sector audits not only function as a financial examination tool, but also as a strategic instrument in promoting sustainable improvement in public financial management.